Penerapan Arsitektur Tropis Pada Perancangan Yoga Retreat Center di Ubud: Bahasa Indonesia - Ida Ayu Wulan Dwi Antari; I Wayan Parwata; Ni Wayan Meidayanti Mustika (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2023)
Indonesia is a country with a tropical climate because of its geographical location on the equator. This causes Indonesia to be affected by 2 seasons, namely the rainy season and the dry season. This situation influences the building design process so that appropriate efforts are needed to overcome the problems encountered in buildings in the tropics. Tropical architecture is an architectural work specifically designed to overcome problems that exist in the tropics. In tropical architecture there are several principles that influence the design of buildings. This principle consists of thermal comfort, air flow through the building, heat radiation, and natural lighting during the day. The Yoga Retreat Center in Ubud is a yoga tourism facility that focuses on accommodating all yoga retreat activities. The location of the site is in the tropics, so it is important to apply tropical architectural principles to the building to create comfort for building users.